PELAKSANAAN SUPERVISI MANAJERIAL OLEH PENGAWAS SEKOLAH DALAM MENINGKATKAN MUTU PENDIDIKAN DI SDN 3 PERCONTOHAN PEUSANGAN KABUPATEN BIREUEN - Agustina Endah Ekawaty; khairuddin .; Sakdiah Ibrahim (Jurnal Administrasi Pendidikan : Program Pascasarjana Unsyiah, 2018)
School supervisors play an active role in realizing the transformation of education quality in their target schools. Managerial supervision by school supervisors is organized to provide services to school administrators so that they can perform their duties effectively and efficiently to achieve learning process quality. In general, this study aimed to describe the implementation of managerial supervision in improving the quality of education at Model Elementary School 3 (SDN 3) of Peusangan, Bireuen regency through the program, implementation of managerial supervision, and constraints experienced by school supervisors in implementing managerial supervision. This research used the descriptive method with the qualitative approach and data collection techniques done for this study were observation, interview, and documentation study. The research subjects are school management personnel consisting of the principal, teachers, administrative staff, librarians, and computer laboratory staff. The results of the study showed that (1) the managerial supervision program includes the guidance activities of teachers and principals, monitoring the implementation of SNP, assessment of teacher performance and principal, as well as mentoring and training of teachers and principal; (2) The success of the managerial supervision process lied in the school supervisors who were able to coordinate and establish cooperative relationships with every well-managed school manager so as to have an impact on improving the quality of education in schools; and (3) the obstacles faced by school supervisors were that they had limited knowledge of the competence of managerial supervision, the school management staff did not meet the required standard requirement both in quantity and skill quality, and supervision schedule which often clashing with official meetings, training and other official activities.Keywords: managerial supervision, school supervisor, and education quality